Implications of SARS-CoV-2 pandemic on pregnancy - Nadia Magallanes-Peláez; Alejandra Mariño-Noya; Nerea Puga-González; Helena Losa-Puig; Laura González-Rodríguez; Emilio Couceiro-Naveira; Carlos López-Ramón y Cajal (Revista Chilena de Obstetricia y Ginecología, 2024)
Introduction: Coronavirus disease (COVID-19) is an infectious disease caused by the SARS-CoV-2 virus. Most people infected with the virus will experience mild to moderate respiratory illness. SARS-CoV-2 is currently a global health issue. Physiological changes due to pregnancy may be related to an increased risk of contracting COVID-19 as well as developing more severe clinical conditions or increasing comorbidities during pregnancy and delivery. Objective: To know the incidence of spontaneous labor and gestational comorbidities during the pandemic. Methods: A retrospective single-centric cohort study was designed using a database from the delivery unit created prospectively. Pregnant women whose pregnancies finished between June 2019 and May 2022 were included. Two groups of pregnant women were defined: group I: “pre-pandemic pregnant women”, whose pregnancies finished between June 2019 and May 2020; and group II: “pandemic pregnant women”, whose pregnancies finished between June 2020 and May 2021. Results: The incidence of spontaneous labor was 49.1% for Group I and 46.4% for Group II (p = 0.602). Group II had higher rates of normal and cesarean section deliveries and lower rates of instrumental deliveries. The incidence of gestational diabetes (GD), hypertension, and preeclampsia was higher, while the incidence of preterm rupture of membranes was lower in the pandemic group. Conclusion: The incidence of GD, hypertension, and preeclampsia increased during the pandemic. The onset of spontaneous labor in pregnancy was similar for both groups.